Occupational Safety and Health Risks in Building Construction Projects : A Systematic Literature Review - Santoso, Imam Sugeng; Noor, Agus Bambang S; Purba, Humiras Hardi (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Although quite a few studies have focused on Occupational Health and Safety (OHS)-related issues within the context of sustainable building construction projects, there has been dearth of a study developing a management framework to comprehensively identify, analyze, evaluate, and control the safety risks threatening the involved Building Construction Workers. Risk is always present in every construction project. Occupational safety and health risks in building construction projects have various risks and are likely to be affected due to their difficulty and multiple operations and threats. Risk factors are divided into three categories, namely internal factors, projects, and external factors. Three categories above is further divided into two technical and non-technical risk. This paper review 40 selected papers that discuss risk identification and risk management in residential construction projects. Risk factors in residential projects are generally very diverse and give us an idea that the interrelationships between the parties with an interest in the project contribute to the risk factors themselves occurring the course of the project. It has been mentioned that the risk factors that occur in residential projects is something that is commonplace in various countries, in this case contributing to the success of the project. Outline on this paper has succeeded in providing information on the extent to which risk factors are currently occurring and there is a high potential for a change in the percentage of risk factors according to the classifications presented in this journal for other construction projects in the future.